Role of Universities in City Renovation and in Shaping Its International Brand: A Case Study of the Polish City of Lodz - Domański, Tomasz (International Studies. Interdisciplinary Political and Cultural Journal, 2017)
This paper aims at highlighting the role of higher education institutions in Lodz in the regeneration of urban space and in building the international brand of a university town. Higher education institutions in Lodz are managers and administrators of many historic buildings that testify to the identity of the city and its rich historic legacy. Besides renovating these buildings, universities provide them with new functions by opening them up to local and international communities. Innovation in regenerating cultural heritage may become a distinguishing feature of both Lodz universities and international city’s brand strategy. The key challenge to Lodz is to complete the global regeneration of a post-industrial city in social, cultural, economic, and spatial dimensions using EU funds.